2002
DOI: 10.1007/s00115-002-1270-y
|View full text |Cite
|
Sign up to set email alerts
|

Das Tourette-SyndromEine Übersicht

Abstract: Tourette's syndrome (TS) is a neuropsychiatric disorder characterised by the occurrence of chronic motor and vocal tics that usually begin in childhood. A prevalence of 4-5/10.000 individuals is estimated. Tourette's syndrome patients frequently show comorbidity with other psychiatric disorders such as obsessive compulsive disorder (OCD), attention deficit hyperactivity disorder (ADHD), anxiety, and affective disorders. Some forms of OCD seem to share a common genetic etiology with TS and to be a facultative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 58 publications
(83 reference statements)
1
3
0
1
Order By: Relevance
“…Some disorders that the present study and smaller prior studies have found to be comorbid with OCD have also been found to be more prevalent in family members of OCD probands who themselves do not have OCD [Lenane et al, 1990;Lilenfeld et al, 1998;Nestadt et al, 2001]. Reciprocally, OCD is found in unusually high numbers of family members with several disorders, including Tourette's disorder, eating disorders, trichotillomania, and bipolar disorder [M. Deibler et al, personal communication;Freeman et al, 2000;Godart et al, 2003;Leckman et al, 2003;Lenane et al, 1992;Riederer et al, 2002;Speranza et al, 2001]. Although formal genetic studies of OCD and comorbidity patterns are just beginning, there are examples from studies of other neuropsychiatric disorders that provide evidence suggesting that distinct genetic subgroups may be identified on the basis of comorbidity, e.g., bipolar disorder with or without comorbid panic disorder [MacKinnon et al, 1997].…”
Section: Comorbidity Implications For Genetic Studiessupporting
confidence: 48%
See 1 more Smart Citation
“…Some disorders that the present study and smaller prior studies have found to be comorbid with OCD have also been found to be more prevalent in family members of OCD probands who themselves do not have OCD [Lenane et al, 1990;Lilenfeld et al, 1998;Nestadt et al, 2001]. Reciprocally, OCD is found in unusually high numbers of family members with several disorders, including Tourette's disorder, eating disorders, trichotillomania, and bipolar disorder [M. Deibler et al, personal communication;Freeman et al, 2000;Godart et al, 2003;Leckman et al, 2003;Lenane et al, 1992;Riederer et al, 2002;Speranza et al, 2001]. Although formal genetic studies of OCD and comorbidity patterns are just beginning, there are examples from studies of other neuropsychiatric disorders that provide evidence suggesting that distinct genetic subgroups may be identified on the basis of comorbidity, e.g., bipolar disorder with or without comorbid panic disorder [MacKinnon et al, 1997].…”
Section: Comorbidity Implications For Genetic Studiessupporting
confidence: 48%
“…A similar but even more marked asymmetry occurs with Tourette's disorder, found in 4-5% of OCD patients in our study and prior studies of OCD comorbidity (Table 1). In contrast, OCD diagnoses are as high as 30-65% in individuals with a primary Tourette's diagnosis [Riederer et al, 2002]. Contemporaneous development of ADHD, motor and vocal tics, and OCD has been described; Tourette's syndrome represents the most severe outcome [Jankovic, 2001].…”
Section: Other Disordersmentioning
confidence: 99%
“…The diagnosis of TS is made with the presence of at least one vocal and two motor tics with an onset before 18 years of age and duration lasting more than a year, given other possible causes have been excluded. TS may also be accompanied by behavioral disturbances [20]. Tics are sudden, intermittent, involuntary, or semi-voluntary movements (motor tics) or sounds (phonic/vocal tics).…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] It has estimated the worldwide prevalence of 4–5/10,000. [ 5 ] It is associated with a wide range of comorbid behavioral abnormalities including attention-deficit hyperactivity disorder in 21%–90%, OCB in 50%, and other anxiety and mood disorders. [ 6 ] However, the incidence of OCB and other mood disorders increases in severe TS.…”
Section: Discussionmentioning
confidence: 99%